2021
DOI: 10.3390/ijerph181910446
|View full text |Cite
|
Sign up to set email alerts
|

An 8-Week Program of Plyometrics and Sprints with Changes of Direction Improved Anaerobic Fitness in Young Male Soccer Players

Abstract: This study examined the effects of 8 weeks of twice-weekly combined plyometric and sprint with change-of-direction (CPSCoD) training into habitual training regimes of young male soccer players. Participants were randomly allocated to an experimental group (n = 17, age: 14.6 ± 0.44 years, body mass: 61.2 ± 7.34 kg, height: 1.67 ± 0.09 m, body fat: 11.2 ± 1.56%) and a control group (n = 16, age: 14.6 ± 0.39 years, body mass: 61.1 ± 3.96 kg, height: 1.67 ± 0.05 m, body fat: 11.8 ± 1.47%). Measures obtained pre- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
1
9
1
1
Order By: Relevance
“…However, this was not the aim of this study. The findings of the present study agree with those of recent research [ 9 , 22 , 23 , 25 ]. However, there are also studies that did not observe an improvement in the performance of COD ability after a plyometric program combined with COD exercises [ 7 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, this was not the aim of this study. The findings of the present study agree with those of recent research [ 9 , 22 , 23 , 25 ]. However, there are also studies that did not observe an improvement in the performance of COD ability after a plyometric program combined with COD exercises [ 7 ].…”
Section: Discussionsupporting
confidence: 94%
“…For this reason, it is a factor that is studied extensively. Recent literature reports the positive effect of plyometrics on speed indicators [ 8 , 9 , 39 ] and combined programs of plyometrics with a change of direction sprints [ 22 , 23 , 25 , 39 ]. However, in the present study, no improvement was observed at 10 m and 30 m.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other aspects of successful performance in team sports such as handball, rugby, volleyball, and basketball depend on the cooperation of team players to score more goals/points than the opposing team. All these team sports involve brief periods of high-intensity activity interspersed with lower-intensity activities that support play as well as provide brief recovery opportunities [ 15 ]. Concerning fatness, recent studies have suggested that anthropometric measurements might be related to physical fitness components in team sports [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, combination training appears en vogue and is an efficacious tool for improving athletic performance. In this context, all of the combined sprint and plyometric (Ferley et al, 2020;Hammami et al, 2020;Kargarfard et al, 2020), agility and balance (Zemková and Hamar, 2010), plyometric and change-ofdirection (Makhlouf et al, 2018;Hammami et al, 2019;Aloui et al, 2021), plyometric and sled (Prieto et al, 2021), balance and plyometric (Bouteraa et al, 2020;Guo et al, 2021), and plyometric and resistance (Almoslim, 2016;Ramirez-Campillo et al, 2018a;Fischetti et al, 2019) training programs have been effective to enhance muscle power. In addition, some recent research has indicated that combined training is superior to stand-alone approaches for increasing power and output capabilities (Chaouachi et al, 2014;Beato et al, 2018;Zghal et al, 2019;Ferley et al, 2020;Guo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%